Exploring assessment practices of teachers in Advanced Speech courses - Tessera, Endalew Molla; Kassa, Animaw Anteneh (ELT Forum: Journal of English Language Teaching, 2024)
In Ethiopia, there is a general public concern that most university students lack communicative competence, and hence they could not communicate effectively in English. There are many contributing factors to this and most of these factors are related either to the curriculum, the teaching-learning process, or the assessment practice. Only a few studies have been conducted on the assessment practice of speaking skills since most researchers have focused on the teaching-learning process. This inquiry was made to look into the practice of assessing the Advanced Speech course. Specifically, it focuses on the assessment methods employed by teachers, the extent of measuring the sub-skills of speaking, and the effectiveness of the feedback given by the teachers. Forty-three students and six teachers were included in the study. Data were collected through in-depth interviews, classroom observation, and document analysis. The findings revealed that not many assessment methods were employed to assess the students. Sixty percent of the assessment of the course was covered by written assignments and a written final exam. Only two individual and group presentations were given as practical assessments. In addition, the assessments did not measure the students’ accuracy, fluency, pronunciation, and vocabulary. In the end, the feedback provided to the students was not effective. Students were not given a chance to correct their own errors, and they were not allowed to practice peer correction, either. This implied that teachers’ assessment practices were not effective to measure the students’ speaking performance in the intended manner and this is one of the factors that minimizes the quality of education.